2004
DOI: 10.1143/jjap.43.6371
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Aluminum Schottky Contact on Plasma-Treated Cadmium Telluride Surface

Abstract: We have studied the effect of plasma treatment on the rectification property and performance of the CdTe radiation detector with the Al Schottky electrode. The Te-rich layer on the CdTe surface etched with Br-methanol caused the degradation of the rectification property of the Al/CdTe Schottky contact. To remove the Te-rich layer, plasma treatment was carried out. The plasma treatment did not roughen the CdTe surface, and it removed the Te-rich layer. In terms of current–voltage characteristics of the Al/CdTe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 14 publications
2
29
0
Order By: Relevance
“…We have found that the property of Schottky contact was improved by plasma treatment and the details are described in our previous paper [3], [4]. An Al Schottky contact was formed on CdTe(111)Te-face by electron-beam evaporating.…”
Section: Detector Fabrication and Measurementmentioning
confidence: 85%
“…We have found that the property of Schottky contact was improved by plasma treatment and the details are described in our previous paper [3], [4]. An Al Schottky contact was formed on CdTe(111)Te-face by electron-beam evaporating.…”
Section: Detector Fabrication and Measurementmentioning
confidence: 85%
“…The electrodes structure is: (top, anode) Au/Pt/CdTe/Al/Ti/Au (bottom, cathode). 5 The negative voltage bias is applied to the anode. Due to high quality of the CdTe crystals and presence of Schottky barrier, the measured total leakage current of the dies (including the guard rings) is from 2 to 3 nA at +10 °C and −100 V bias (from 232 to 348 pA/cm 2 ).…”
Section: Cdte Diementioning
confidence: 99%
“…This diffusion of indium leads to a lack of electrical isolation of the pixels compromising the detector performance. As an alternative, some manufacturers use aluminium to form a Schottky contact, these have improved stability but suffer from poorer leakage current performance in comparison to indium contacts [13], [14]. 0018-9499/$31.00 © 2012 IEEE Rather than use standard photolithography, it is possible to segment the indium anode using a diamond blade.…”
Section: Edgeless Cadmium Telluride Detectorsmentioning
confidence: 99%